2019
DOI: 10.4103/apc.apc_123_13
|View full text |Cite
|
Sign up to set email alerts
|

Ventricular arrhythmia: A feature of tubercular myocarditis

Abstract: Tuberculat myocarditis is an extremely rare entity with few published reports. We report a 13 year old male who presented with ventriculat tachycardia. On evaluation he was observed to have MRI features and workup consistent with nodular variant of tubercular myocarditis. Child had fatal outcome on follow up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Sudden cardiac death related to tuberculosis is also being increasingly reported. Cardiac complications occur rarely but they are potentially treatable, and early recognition of the underlying cause is key to timely management [1]. Michira et al conducted a systematic review of cases including tuberculous myocarditis and pericarditis and found that in 81% of the cases, tuberculous myocarditis was reported in immunocompetent patients below 45 years of age.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden cardiac death related to tuberculosis is also being increasingly reported. Cardiac complications occur rarely but they are potentially treatable, and early recognition of the underlying cause is key to timely management [1]. Michira et al conducted a systematic review of cases including tuberculous myocarditis and pericarditis and found that in 81% of the cases, tuberculous myocarditis was reported in immunocompetent patients below 45 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Although tuberculosis is primarily a pulmonary disease, however, it may involve other extrapulmonary organs as well including the heart. Isolated myocardial involvement in tuberculosis is exceedingly rare; several reports suggest that it can present with atrioventricular block, ventricular arrhythmias, congestive cardiac failure, or sudden cardiac death [1]. Tuberculous myocarditis is associated with high mortality and is often diagnosed during post-mortem examination because of the low index of suspicion and insidious course.…”
Section: Introductionmentioning
confidence: 99%
“…Myocardial involvement in tuberculosis is considered extremely rare; most initial publications consisted of single case reports 3,4,5 . Liu et al in 2012 reviewed the association between cardiac tuberculosis and sudden cardiac death, emphasizing that this is a diagnosis confirmed on postmortem 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Myocardial involvement is extremely rare and limited to sparse case reports 3,4,5 . We present a case series of four patients, in whom a high index of suspicion, detailed work‐up, and early, appropriate therapy led to a positive clinical outcome.…”
Section: Introductionmentioning
confidence: 93%
“…The first case of cardiac TB was reported in 1664, and the second, 97 years later, was identified in 1761.There are just a few occurrences of the same, therefore it is crucial to know what you are looking for. (1) Infections, autoimmune illnesses, and toxic chemicals can all cause myocarditis, which is an inflammatory condition of the heart muscle. It is a leading cause of untimely mortality among young adults.…”
Section: Introductionmentioning
confidence: 99%